Aggregatibacter aphrophilus infective endocarditis confirmed by broad-range PCR diagnosis: A case report. (2017) - Hirano, Koji; Tokui, Toshiya; Inagaki, Masahiro; Fujii, Taro; Maze, Yasumi; Toyoshima, Hirokazu
Highlights: Case of infective endocarditis caused by a rare pathogen, Aggregatibacter aphrophilus is presented. Aggregatibacter aphrophilu s can't be detected by common culture methods. Br-PCR testing is a useful tool to identify pathogens of culture negative endocarditis. Serum PR3-ANCA can be positive in Aggregatibacter aphrophilus endocarditis. Abstract: Introduction: Aggregatibacter aphrophilus is a rare cause of infective endocarditis. This pathogen is difficult to identify with common culture methods, which can lead to incorrect diagnosis and treatment. Presentation of case: A 72-year-old woman was admitted to a community hospital with a persistent high fever and deteriorating renal function. Based on negative blood culture and positive serum proteinase 3 anti-neutrophil cytoplasmic antibody (PR3-ANCA), acute renal failure associated with ANCA-rerated vasculitis was initially suspected. However, the patient developed heart failure soon afterward; echocardiography showed mitral insufficiency with mobile vegetation attached to the mitral valve, indicating infective endocarditis. After transfer to our hospital, the patient underwent mitral valve repair. Broad-range polymerase chain reaction (br-PCR) and sequencing identified Aggregatibacter aphrophilus in the excised vegetation. The patient had a good postoperative course, with recovery of renal function. Conclusion: A rare disease, Aggregatibacter aphrophilus infective endocarditis was successfully treated with surgical repair and appropriate antibiotic therapy. To avoid misdiagnosis, br-PCR testing should be performed in patients with blood culture-negative endocarditis.